Patent law versus competition law in the European Union: a complementary relationship? - Martínez Pérez, Miriam (CUADERNOS DE DERECHO TRANSNACIONAL, 2018)
Relationships between Patent law and Competition law in European Union law are in constant tension. In many cases, it is really difficult to determine where the scope of the action of one ends and where the application of the other begins. Thus, the need to analyse the difficult coexistence of these two sectors of the legal system arises in order to determine whether there is a complementary relationship between them or whether, on the contrary, they are antagonistic regulations. This paper will be dedicated to the study of these issues.
Keywords: Patent law; Competition law; complementary relationship; anticompetitive behaviour; ex ante and ex post corrective tools